ANALYSIS OF ECONOMIC MINERAL AVAILABILITY USING THE LINEAMENT DENSITY METHOD AROUND PANGKALAN JAMBU DISTRICT, MERANGIN REGENCY, JAMBI PROVINCE - MAULANA DIMAS KIRANA; HURIEN HELMI; OBRIN TRIANDA (ReTII, 2021)
One area that is famous for the existence of gold mines owned by the people in Jambi Province is in Merangin Regency, more precisely around Pangkalan Jambu District. The presence of gold mines around the research area indicates the result of hydrothermal alteration in the form of gold deposits. The use of geographic information systems aims to determine the location of the lineament density zone which is estimated to be the source of hydrothermal alteration. The purpose of this study is to model lineament density by utilizing secondary data in the form of DEM data which is added with hillshade to extract lineaments, then combined with structure on lineaments based on Regional Geological Maps. The results showed that high and medium density zones were located in areas associated with fault zones, which is one of the strong factors for the presence of alteration in areas that have a strong structural density or crushed zone. It is known that the majority of mines are in the medium-low density zone close to the river flow, this can happen because the river passes through several density zones at once can be used as a transportation medium for materials that have experienced erosion so that they can be deposited in areas that are currently under water. mine. It is known that there is potential for alteration in 2 zones of medium and high density, each having an estimated area of ​​4130.50 Ha in the high density zone and 49557.53 Ha in the medium density zone.